Practice recommendations for neurovascular ultrasound investigations of acute stroke patients in the setting of the COVID‐19 pandemic: an expert consensus from the European Society of Neurosonology and Cerebral Hemodynamics. (18th June 2020) - Baracchini, C.; Pieroni, A.; Kneihsl, M.; Azevedo, E.; Diomedi, M.; Pascazio, L.; Wojczal, J.; Lucas, C.; Bartels, E.; Bornstein, NM.; Csiba, L.; Valdueza, J.; et al.
Abstract : Background and purpose: Patients with acute ischemic stroke are at high‐risk for contracting COVID‐19 infection. Additionally, healthcare professionals including neurovascular ultrasound providers are also at risk of being infected by SARS‐CoV‐2 virus. Yet, preparedness to continue to guarantee hyperacute treatment is vital for patients outcome. In light of this situation, the European Society of Neurosonology and Cerebral Hemodynamic (ESNCH) appointed a task force to provide consensus recommendations for the performance of neurovascular ultrasound investigations in acute ischemic stroke during the COVID‐19 pandemic with the aim of protecting both patients and ultrasound providers. Methods: The "ultrasound in acute stroke working group" of the ESNCH examined literature articles and reviews using the following key words: "corona virus" or "COVID‐19" or "SARS‐CoV‐2 virus", and "acute stroke" or "cerebrovascular disease", and "ultrasound". Thereafter, a thorough discussion was conducted with the "education and guidelines working group" of the ESNCH. Results: We propose rapid up‐to‐date recommendations for healthcare personnel involved in the pre‐hospital and intra‐hospital assessment of stroke patients, with a particular attention to neurovascular ultrasound performance. Conclusion: The ESNCH provides a guidance summary for the performance of neurovascular ultrasound investigations in acute ischemic stroke in the time of COVID‐19.